Rapid mammal survey at Batu Caves, Selangor, Malaysia, with notes on other fauna - Priscillia Miard; Nik Fadzly Nik Rosely; Nadine Ruppert (Malaysian Nature Society, 2023)
A number of isolated patches of forest in Malaysia are understudied but potentially host a high species diversity and endemism. The aim of this study was to assess the presence of mammal species at different locations on the limestone hills located at Batu Caves, Selangor. We undertook transects walks along trails in two locations around the hill for four hours maximum at sunset and sunrise for five days (24 to 26 June 2019 and 15 to 16 October 2019). We recorded six species of diurnal mammals: Callosciurus notatus, Macaca fascicularis, Sundasciurus hippurus, Sundasciurus lowii, Trachypithecus obscurus and Tupaia glis. We also spotted two species of nocturnal mammals: Leopoldamys sabanus, and Paradoxurus hermaphroditus, and heard one, Capricornis sumatraensis. Additionally, we recorded five species of nocturnal birds including four species of owls, Caprimulgus macrurus, Ninox scutulata, Otus lempiji, Otus lettia and Tyto alba. We also heard Argusianus argus and sighted Cuora amboinensis kamaroma. This short survey detected rare and endangered species emphasizing the need for future in-depth research in this isolated forest on limestone area.